1976
DOI: 10.1063/1.433256
|View full text |Cite
|
Sign up to set email alerts
|

Infrared matrix study of reactions of UF4 with fluorine

Abstract: Chemical reactions between UF4 and fluorine to produce UF5 and UF6 were studied by the technique of matrix isolation and observation of infrared spectra of reacting species in the matrix.(AIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Also the infrared spectra of UF 4 were measured by Kunze et al [13,14] and Bukhmarina et al [15][16][17]. They observed a large number of absorption bands in the far-infrared at about 101 cm À1 and the stretching region at about 540 cm À1 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also the infrared spectra of UF 4 were measured by Kunze et al [13,14] and Bukhmarina et al [15][16][17]. They observed a large number of absorption bands in the far-infrared at about 101 cm À1 and the stretching region at about 540 cm À1 .…”
Section: Introductionmentioning
confidence: 98%
“…The uranium tetrahalides play important roles in nuclear fuel enrichment and reprocessing [1], which have been studied in detail both in the solid state [2] and the gas phase [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The first experimental electron diffraction studies of the uranium tetrahalides date from 1958 and were interpreted as regular tetrahedral geometries [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 1 F product species was probably formed by a gasphase reaction between F 2 and UC1 4 before the matrix can quench the excess internal energy of UC1 4 which was vaporized at 415-445°C. In the matrix IR study on fluorination of UF 4 [1], both UF 5 and UF 6 were formed during the codeposition. Since the 1 F absorption was unchanged by the photolysis which promotes the addition of two F atoms to UC1 4 , the 1 F product is most likely due to a single F atom addition to UC1 4 , and the 1 /"band has been assigned to the UC1 4 F. The structure of UC1 4 F cannot be determined from the single 1 F absorption.…”
Section: Uci4f Trans-ucl 4 F 2 and Cis-ucl 4 Fmentioning
confidence: 99%
“…Earlier matrix isolation infrared studies [1,2] on the UF 4 reaction with F 2 and Cl 2 have observed several U -F modes for UF 5 , UF 4 C1, and UF 4 C1 2 . Similarly, UF5CI along with excess UF 6 has been isolated in various matrices and characterized using infrared spectroscopy [3].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation